Communicating tokenomics and monetary policy: A comparative analysis of real and virtual economies - Kane Falco ter Veer; Timo Heinrich (International Journal of Finance & Economics, 2024)
This article investigates the economic governance of blockchain-based virtual economies in the context of monetary policy. Focusing on tokenomics communication, we employ deductive and inductive approaches, applying real-world monetary policy metrics and text mining frameworks. Our comparative analysis reveals that the tokenomics communication in blockchain-based virtual economies primarily functions as a fundraising tool, lacking policy discussions, with divergences from real-world economies in policy goals and numerical targets. Furthermore, our research highlights similarities between blockchain-based virtual economies and early-stage low-income developing countries in communication dynamics.
Keywords: 330; blockchain; monetary policy communication; monetary policy frameworks; text mining; tokenomics; virtual economies